Unregistered Polygamy Among Public Figures: A Socio-Legal Analysis of Marital Consent and Islamic Family Law in Indonesia - Susi Kusmawaningsih; Destri Natalia; Chairul Musthopa (Nuris Journal of Education and Islamic Studies, 2026)
The issue of unregistered polygamous marriage without the consent of the first wife continues to generate debate within the discourse of Islamic family law in Indonesia, particularly when such practices involve public figures whose personal actions attract broad public attention. This study aims to analyze the legal status and socio-legal implications of unregistered polygamous marriages conducted without the consent of the first wife within the framework of Indonesian Islamic family law. The research employs a qualitative approach using a socio-legal method that combines doctrinal analysis of legal regulations with an examination of social dynamics surrounding the practice of marriage. The study focuses on the interaction between Islamic jurisprudential principles, national marriage legislation, and public discourse, with particular reference to the public controversy involving Inara Rusli and Insanul Fahmi. The findings show that Indonesian marriage law, particularly Law No. 1 of 1974 and the Compilation of Islamic Law, establishes a regulatory framework that permits polygamy under strict conditions, including judicial approval, financial capability, and the consent of the first wife. However, the practice of unregistered marriage allows individuals to bypass these legal requirements, creating a gap between religious legitimacy and legal recognition. When such practices involve public figures, the issue often evolves into a broader public debate concerning the relationship between religious norms, state legal authority, and social perceptions of marriage. The study concludes that strengthening legal awareness and ensuring compliance with marriage registration procedures are essential for protecting family rights and maintaining legal certainty within Indonesian Islamic family law